Limits and Use of European Union Competences: General Considerations in the Context of Policies on Border Checks, Asylum, and Immigration - Oręziak, Bartłomiej (Migration and Central Europe: Challenges and Legal Responses, 2024)
Competences of the European Union have recently become an increasingly interesting issue from a scientific viewpoint. This is primarily because of the lawmaking activity of European Union institutions, particularly the Court of Justice of the European Union and European Commission. This study aims to analyse the boundaries and rules for exercising the European Union competences in the field of migration and refugee law. The key for this analysis is the principle of conferral, which is of fundamental importance for the limits of European Union competences because of the sovereignty of the subjects of public international law. Moreover, the principles of proportionality and subsidiarity are invoked as determinants for exercising European Union competences. This study explains the meaning of these three principles, particularly focusing on the treaty image of the principle of conferral in the European Union. In this context, it also presents the phenomenon of competence creep described in the literature. The analysis is based on the primary law of the European Union, especially the relevant provisions of the Treaty on European Union and Treaty on the Functioning of the European Union, as a model for the scope of sovereign states’ consent while considering the principle of conferral. Further, the study analyses the secondary law of the European Union regarding its compliance with the primary law, specifying the scope of the European Union’s competences and determining current European Union standards for border checks, asylum, and immigration policies. Consequently, it analyses the decision-maker’s choice regrading compliance of the detailed scope of the European Union competences when encountering doubts that cannot be resolved using a literal or systemic interpretation, that is, where it is necessary to refer to a purposive interpretation. The study concludes with a concise summary proposing how to solve the identified problem. Keywords: EU competences, migration law, refugee law, principle of conferral, principle of subsidiarity, principle of proportionality, competence creep